Teleworking and the challenges for worker protection: reflections on the extension of fundamental labor rights - Pagani , Marcella; Duarte, Giovanna Chagas; Gomes, Sâmara Talita de Oliveira (Seven Editora, 2023)
The competitiveness of the market, the advance of capitalism, and the new digital technologies have made business organizations change the productive mode, as well as the inter-company relationship and work relations, reviewing concepts and paradigms that were petrified before. This article aims to confront the new perspective of teleworking and the guarantee of fundamental labor rights, through the contemporary understanding of the fundamental right to decent work, aiming at preserving workers’ health in a socio-environmental dimension. The proposed investigation is legal-descriptive, aiming at decomposing a legal problem into its various aspects, relationships, and levels. In case, the object is the current analysis and understanding of the challenges of protecting teleworkers in a socio-environmental dimension of decent work. It is intended to demonstrate the extension of fundamental labor rights to the teleworker, to promote the improvement of the worker’s living conditions, curbing social marginality. DOI: https://doi.org/10.56238/devopinterscie-067